The relationship between psychological capital, burnout and perceived stress in junior nurses: a latent profile analysis - Zhang, Xu; Chen, Siye; Zheng, Ziling; Zhao, Mi; Song, Li; Zhao, Yue; Wang, Zhiwen (Frontiers in Public Health, 2024)
Background: Psychological capital, an intrinsic personal asset, enhances junior nurses' ability to navigate transition and sustain superior job performance. This study aimed to classify junior nurses into distinct psychological capital profiles and examine their associations with burnout and perceived stress levels.A cross-sectional study involving 480 junior nurses from three hospitals in Beijing assessed psychological capital, stress, and burnout using e-questionnaires, from July 2021 to August 2022. We employed exploratory latent profile analysis for psychological capital profiling and logistic regression with the best subset method to identify the influential factors.The results of the latent profile analysis supported the models of two latent profiles, which were defined as low psychological capital (224, 46.5%) and high psychological capital (256, 53.5%).Logistic regression revealed that introverted nurses and those experiencing moderate to high levels of burnout and stress were more likely to exhibit low psychological capital.Nursing management should proactively identify and support junior nurses with low psychological capital, with a focus on introverted individuals, to mitigate the impact of stress and burnout.